2015
DOI: 10.1016/j.yhbeh.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Surprising origins of sex differences in the brain

Abstract: Discerning the biologic origins of neuroanatomical sex differences has been of interest since they were first reported in the late 60’s and early 70’s. The centrality of gonadal hormone exposure during a developmental critical window cannot be denied but hormones are indirect agents of change, acting to induce gene transcription or modulate membrane bound signaling cascades. Sex differences in the brain include regional volume differences due to differential cell death, neuronal and glial genesis, dendritic br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 89 publications
(115 reference statements)
5
97
0
Order By: Relevance
“…These findings corroborate those of Lenz et al, (2013), who found microglia to be a key mediator of the masculinization of sex behaviors. Our understanding of how microglia may mediate organizational sex differences in the brain is still in its infancy, but interestingly, many of the mechanisms by which sex differences are established are also developmental processes that are heavily influenced by microglia (Lenz and McCarthy, 2015; McCarthy et al, 2015). Further investigation into how microglia may act to sculpt sexually dimorphic circuitry in the brain is critical to advancing our understanding of a fundamental aspect of brain development.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate those of Lenz et al, (2013), who found microglia to be a key mediator of the masculinization of sex behaviors. Our understanding of how microglia may mediate organizational sex differences in the brain is still in its infancy, but interestingly, many of the mechanisms by which sex differences are established are also developmental processes that are heavily influenced by microglia (Lenz and McCarthy, 2015; McCarthy et al, 2015). Further investigation into how microglia may act to sculpt sexually dimorphic circuitry in the brain is critical to advancing our understanding of a fundamental aspect of brain development.…”
Section: Discussionmentioning
confidence: 99%
“…This statement preceded by a decade the discipline of neuroscience, which was not firmly established as an independent field until the 1970s. In the time since then, extensive research on animal models irrefutably established that gonadal hormone secretions from the male testis early in development act on the brain to masculinize it (reviewed in [14][15][16][17]). In rodents, the androgens produced by the testis are aromatized to oestrogens, an essential step in the masculinization process, whereas, in primates, androgens act directly (reviewed in [18]).…”
Section: A Brief History Of the Study Of Brain Sex Differencesmentioning
confidence: 99%
“…This is supported by a wealth of research highlighting critical sex differences in downstream targets of this axis, including neuroendocrine and neuroimmune systems [53,54]. For instance, female-biased prevalence in functional gastrointestinal disorders, such as irritable bowel syndrome, may result from sex differences in gastrointestinal transit time, visceral sensitivity, central nervous system pain processing and hormonedependent effects on gut physiology [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%